Use of Biologically Active 3D Matrix for Extensive Skin Defect Treatment in Veterinary Practice: Case Report - Zakirova, Elena Yu; Shalimov, Dmitry V.; Garanina, Ekaterina E.; Zhuravleva, Margarita N.; Rutland, Catrin S.; Rizvanov, Albert A. (Frontiers in Veterinary Science, 2019)
Objectives: Large full-thickness skin defects represent a serious veterinary problem. Methods: We have developed novel bioactive 3D-matrixes based on fibrin glue Tissucol (Baxter), containing the combination of the adenoviral constructs with genes vascular endothelial growth factor 165 (VEGF165) and fibroblast growth factor two (FGF2; construct Ad5-VEGF165 + Ad5-FGF2) or multipotent mesenchymal stem cells, genetically modified with these constructs. Results:In vitro studies confirmed the biosynthesis of VEGF165 and FGF2 mRNA in the transduced cells. Ad5-VEGF165 + Ad5-FGF2- transduced multipotent mesenchymal stem cells showed an enhanced capacity to form capillary-like tubes in vitro. Bioactive 3D-matrix application enhanced granulation tissue formation and epithelialization of non-healing, large bite wounds in a dog. Successful wound healing was observed with a positive clinical outcome for the canine patient. This research and application of regenerative gene therapy alongside a novel bioactive 3D-matrix shows promising clinical applications for the future in both dogs and other mammals including humans.